Real stone paint and preparation method thereof
By modifying natural stone powder with homemade water-resistant and UV-resistant polyacrylate emulsion and silane coupling agent, a real stone paint with uniform components and excellent UV-resistant properties was prepared, which solved the problem of existing real stone paint discoloration under direct sunlight and improved its water resistance and service life.
Patent Information
- Application Number
- CN202411783146.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-06
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of decorative coatings, and in particular, relates to real stone paint and a preparation method thereof. Background Art
[0002] Real stone paint is a high-end building decoration material. Its main raw materials are natural white sand, natural colored sand, pigments and synthetic resin emulsion. After curing, it has a texture and color similar to natural stones such as marble and granite, giving the building a natural, atmospheric and high-end appearance. It is widely used in the exterior wall decoration of buildings. The construction process of real stone paint is relatively simple, and it can adapt well to the decoration requirements of exterior walls of buildings with different shapes.
[0003] Real stone paint has excellent weather resistance, but it is easy to change color when exposed to direct sunlight for a long time. This is because the raw materials of real stone paint contain a large amount of synthetic resins. These resins change their molecular structure and turn yellow after being exposed to ultraviolet rays, which greatly affects the decorative effect of the real stone paint. In the prior art, small molecule ultraviolet absorbers are usually added to real stone paint, but small molecule ultraviolet absorbers are easy to migrate during use and are difficult to be effective for a long time. The repair process of real stone paint is relatively complicated. Therefore, at this stage, a real stone paint with excellent ultraviolet resistance is urgently needed. Based on this, the present invention provides a real stone paint and a preparation method thereof. Summary of the invention
[0004] The object of the present invention is to provide a real stone paint and a preparation method thereof, so as to solve the problems mentioned in the above background technology.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A real stone paint comprises the following raw materials in parts by weight: 90-120 parts of natural stone powder, 70-100 parts of water-resistant and UV-resistant polyacrylate emulsion, 10-14 parts of propylene glycol methyl ether acetate, 2.4-4.8 parts of dispersant, 6-8 parts of silane coupling agent KH-570, 8-12 parts of bentonite, and 15-28 parts of deionized water;
[0007] A method for preparing real stone paint comprises the following steps:
[0008] The first step is to weigh the raw materials according to the mass proportions: 90-120 parts of natural stone powder, 70-100 parts of water-resistant and UV-resistant polyacrylate emulsion, 10-14 parts of propylene glycol methyl ether acetate, 2.4-4.8 parts of dispersant, 6-8 parts of silane coupling agent KH-570, 8-12 parts of bentonite, and 15-28 parts of deionized water;
[0009] Step 2: Mix silane coupling agent KH-570, natural stone powder and ethanol solution in a container, and heat and stir to obtain modified stone powder;
[0010] Step 3: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, a dispersant, and deionized water in a container, and stir to obtain a prefabricated liquid;
[0011] The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, stir and disperse, then add bentonite to the solution, continue to stir and mix evenly to obtain a real stone paint.
[0012] Furthermore, the natural stone powder is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:1.1-2.4.
[0013] Furthermore, the dispersant is sodium lignin sulfonate.
[0014] Furthermore, the ethanol solution used in the second step is an ethanol aqueous solution with a volume fraction of 90%, and the mass ratio of the silane coupling agent KH-570 used in the second step, the natural stone powder, and the ethanol solution is 6-8:90-120:60-80.
[0015] Furthermore, the heating and stirring conditions in the second step are stirring at a temperature of 40-60° C. for 2-4 hours.
[0016] Furthermore, in the third step, the rotation speed of the stirring and mixing is 1600-2000 rpm, and the time of the stirring and mixing is 90-120 min.
[0017] Furthermore, in the fourth step, the rotation speed of the first stirring and dispersing is 1200-1600 rpm, and the time condition is 60-90 min. The rotation speed condition of the second stirring is 600-800 rpm, and the time condition is 30-50 min.
[0018] Furthermore, the water-resistant and UV-resistant polyacrylate emulsion is prepared by the following steps:
[0019] Step 1, benzotriazole, allyl alcohol, and 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine are mixed in a three-necked flask, a condenser and a thermometer are installed, magnetic stirring is turned on, and the mixture is reacted at a temperature of 40-60° C. for 20-24 hours. After the reaction is completed, deionized water is added to the three-necked flask for washing, and the mixture is extracted with dichloromethane. The organic layer is then separated with a separatory funnel, and the organic layer is rotary evaporated to obtain intermediate 1;
[0020] Step 2, mix the intermediate 1, acryloyl chloride, triethylamine and N,N-dimethylformamide in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 30-60°C for 1-2h. After the reaction is completed, add deionized water to the three-necked flask for washing, extract with ethyl acetate, separate the organic layer with a separatory funnel, and rotary evaporate the organic layer to obtain the intermediate 2;
[0021] Step 3, anhydrous ethanol, diethylene glycol butyl ether, and azobisisobutyronitrile are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Then, the system temperature is raised to 78°C, and a self-made mixed solution is added dropwise to the three-necked flask with a high-pressure dropping pump. The dropping time is 1.5-2h, and the temperature is controlled at 78-82°C during the dropping. After the dropping is completed, the reaction is continued for 1.5-2h. After the reaction is completed, the system temperature is lowered to 45-55°C, and N,N-dimethylethanolamine is added to the three-necked flask for neutralization, and deionized water is added for emulsification to obtain the water-resistant and UV-resistant polyacrylate emulsion.
[0022] Furthermore, the amount ratio of benzotriazole, allyl alcohol and 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine used in step 1 is 0.1 mol: 0.1 mol: 0.18 g.
[0023] Furthermore, the intermediate 1 used in step 2, acryloyl chloride, triethylamine, and N,N-dimethylformamide are mixed in a three-necked flask at 0.08 mol: 0.09-0.11 mol: 0.12 mol: 40-60 mL.
[0024] Furthermore, the homemade mixed solution used in step 3 is prepared from 4-6 g of intermediate 2, 3-5 g of hexafluorobutyl acrylate, 45-50 g of methyl methacrylate, 1.5-2.5 g of methacrylic acid, 25-30 g of butyl acrylate and 1.2-2.4 g of azobisisobutyronitrile.
[0025] Furthermore, the dosage ratio of anhydrous ethanol, diethylene glycol butyl ether, azobisisobutyronitrile, homemade mixed solution, N,N-dimethylethanolamine, and deionized water used in step 3 is 24-36g: 3-4g: 0.8-1.6g: 79.7-95.9g: 1.2-2g: 36-44g.
[0026] Beneficial effects of the present invention:
[0027] 1) The present invention uses natural stone powder, self-made water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant, silane coupling agent KH-570, bentonite and deionized water as raw materials to prepare a real stone paint. The present invention first modifies the natural stone powder with a silane coupling agent KH-570, then dissolves and mixes the water-resistant and UV-resistant polyacrylate emulsion and propylene glycol methyl ether acetate with deionized water to prepare a prefabricated liquid, and finally adds the modified stone powder and bentonite to the prefabricated liquid respectively and stirs and mixes to obtain a real stone paint; the preparation method of the present invention uses a silane coupling agent to modify the natural stone powder, the modified natural stone powder has good bonding with the radical resin, and the prepared real stone paint has uniform components, few defects after curing, and is not easy to crack.
[0028] 2) The present invention uses benzotriazole and allyl alcohol as raw materials, and the amino group of benzotriazole and the double bond of allyl alcohol undergo Michael addition reaction under the catalytic action of 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine to obtain intermediate 1, and then uses intermediate 1 and acryloyl chloride as raw materials, and the hydroxyl group of intermediate 1 and the acyl chloride group of acryloyl chloride undergo esterification reaction under the condition of triethylamine as an acid-binding agent to obtain intermediate 2, and finally intermediate 2 and hexafluorobutyl acrylate, methyl methacrylate, methacrylic acid, and butyl acrylate are catalyzed by an initiator azobisisobutyronitrile to obtain intermediate 2. Polymerization occurs to obtain a water-resistant and UV-resistant polyacrylate emulsion, wherein the intermediate 2 has an acrylic ester structure and has good similarity with other polymerized monomers, and the intermediate 2 is connected with a benzotriazole structure and has good absorption effect on ultraviolet rays. Compared with the addition method of small molecule blending, the water-resistant and UV-resistant polyacrylate emulsion prepared by the preparation method of the present invention has a more stable UV absorption capacity and is not easy to migrate. In addition, the polyacrylate emulsion structure of the present invention contains a large number of carbon-fluorine bonds, and these carbon-fluorine bonds have extremely low surface energy, have a good repelling effect on water molecules, and can show an obvious hydrophobic effect.
[0029] 3) The real stone paint of the present invention is beautiful and has uniform components. It is not easy to crack after curing, has good water resistance and excellent UV resistance, and can be widely used in the field of architectural decoration. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Example 1
[0032] A water-resistant and UV-resistant polyacrylate emulsion is prepared by the following steps:
[0033] Step 1, 0.1 mol of benzotriazole, 0.1 mol of allyl alcohol, and 0.18 g of 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 40° C. for 20 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0034] Step 2, 0.08 mol of intermediate 1, 0.09 mol of acryloyl chloride, 0.12 mol of triethylamine, and 40 mL of N,N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 30°C for 1 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with ethyl acetate. The organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2;
[0035] Step 3, 24g of anhydrous ethanol, 3g of diethylene glycol butyl ether, and 0.8g of azobisisobutyronitrile are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Then, the system temperature is raised to 78°C, and 79.7g of the homemade mixed solution is added dropwise to the three-necked flask with a high-pressure dropping pump. The dropping time is 1.5h, and the temperature is controlled at 78-82°C during the dropping. After the dropwise addition is completed, the reaction is continued for 1.5h. After the reaction is completed, the system temperature is lowered to 45°C, and 1.2g of N,N-dimethylethanolamine is added to the three-necked flask for neutralization, and 36g of deionized water is added for emulsification to obtain the water-resistant and UV-resistant polyacrylate emulsion.
[0036] The self-made mixed solution is prepared from 4g of intermediate 2, 3g of hexafluorobutyl acrylate, 45g of methyl methacrylate, 1.5g of methacrylic acid, 25g of butyl acrylate and 1.2g of azobisisobutyronitrile.
[0037] Example 2
[0038] A water-resistant and UV-resistant polyacrylate emulsion is prepared by the following steps:
[0039] Step 1, 0.1 mol of benzotriazole, 0.1 mol of allyl alcohol, and 0.18 g of 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 50° C. for 22 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0040] Step 2, 0.08 mol of intermediate 1, 0.1 mol of acryloyl chloride, 0.12 mol of triethylamine, and 50 mL of N,N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 45°C for 1.5 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with ethyl acetate. The organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2;
[0041] Step 3, 30g of anhydrous ethanol, 3.5g of diethylene glycol butyl ether, and 1.2g of azobisisobutyronitrile are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Then, the system temperature is raised to 78°C, and 87.8g of the homemade mixed solution is added dropwise to the three-necked flask with a high-pressure dropping pump. The dropping time is 1.75h, and the temperature is controlled at 78-82°C during the dropping. After the dropwise addition is completed, the reaction is continued for 1.75h. After the reaction is completed, the system temperature is lowered to 50°C, and 1.6g of N,N-dimethylethanolamine is added to the three-necked flask for neutralization, and 40g of deionized water is added for emulsification to obtain the water-resistant and UV-resistant polyacrylate emulsion.
[0042] The self-made mixed solution is prepared from 5g of intermediate 2, 4g of hexafluorobutyl acrylate, 47.5g of methyl methacrylate, 2g of methacrylic acid, 27.5g of butyl acrylate and 1.8g of azobisisobutyronitrile.
[0043] Example 3
[0044] A water-resistant and UV-resistant polyacrylate emulsion is prepared by the following steps:
[0045] Step 1, 0.1 mol of benzotriazole, 0.1 mol of allyl alcohol, and 0.18 g of 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 60° C. for 24 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with dichloromethane. The organic layer was then separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 1;
[0046] Step 2, 0.08 mol of intermediate 1, 0.11 mol of acryloyl chloride, 0.12 mol of triethylamine, and 60 mL of N,N-dimethylformamide were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the mixture was reacted at 60°C for 2 h. After the reaction was completed, deionized water was added to the three-necked flask for washing, and the mixture was extracted with ethyl acetate. The organic layer was separated with a separatory funnel, and the organic layer was rotary evaporated to obtain intermediate 2;
[0047] Step 3, 36g of anhydrous ethanol, 4g of diethylene glycol butyl ether, and 1.6g of azobisisobutyronitrile are mixed in a three-necked flask, a condenser and a thermometer are installed, and magnetic stirring is turned on. Then, the system temperature is raised to 78°C, and 95.9g of the homemade mixed solution is added dropwise to the three-necked flask with a high-pressure dropping pump. The dropping time is 2h, and the temperature is controlled at 78-82°C during the dropping. After the dropping is completed, the reaction is continued for 2h. After the reaction is completed, the system temperature is lowered to 55°C, and 2g of N,N-dimethylethanolamine is added to the three-necked flask for neutralization, and 44g of deionized water is added for emulsification to obtain the water-resistant and UV-resistant polyacrylate emulsion.
[0048] The self-made mixed solution is prepared from 6g of intermediate 2, 5g of hexafluorobutyl acrylate, 50g of methyl methacrylate, 2.5g of methacrylic acid, 30g of butyl acrylate and 2.4g of azobisisobutyronitrile.
[0049] Experimental Example 1
[0050] After the water-resistant and UV-resistant polyacrylate emulsions obtained in Examples 1-3 were cured, the water contact angles were tested using an OCA50 contact angle surface tester sold by Dataphysics of Germany. The test results are shown in Table 1:
[0051] Table 1
[0052]
[0053] It can be seen from Table 1 that the water contact angles of the water-resistant and UV-resistant polyacrylate emulsions prepared by the present invention after curing are all greater than 90°, showing good hydrophobicity. After contacting rainwater, since the base resin has good hydrophobicity, water droplets cannot wet the surface of the real stone paint, and the prepared real stone paint also has good water resistance.
[0054] Example 4
[0055] A real stone paint comprises the following raw materials in parts by weight: 90 parts of natural stone powder, 70 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 1, 10 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 6 parts of silane coupling agent KH-570, 8 parts of bentonite, and 15 parts of deionized water;
[0056] A method for preparing real stone paint comprises the following steps:
[0057] The first step is to weigh the raw materials by mass: 90 parts of natural stone powder, 70 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 1, 10 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 6 parts of silane coupling agent KH-570, 8 parts of bentonite, and 15 parts of deionized water;
[0058] Step 2: Mix silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume in a container, and stir for 2 hours at 40°C to obtain modified stone powder, wherein the mass ratio of silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume is 6:90:60;
[0059] Step 3: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant and deionized water obtained in Example 1 in a container, and stir at a speed of 1600 rpm for 90 min to obtain a prefabricated liquid;
[0060] The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, and stir at a speed of 1200 rpm for 60 minutes to disperse, then add bentonite to the solution, and continue to stir at a speed of 600 rpm for 30 minutes to mix evenly to obtain a real stone paint.
[0061] The natural stone powder in this embodiment is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:1.1.
[0062] Example 5
[0063] A real stone paint, comprising the following raw materials in parts by weight: 105 parts of natural stone powder, 85 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 2, 10 parts of propylene glycol methyl ether acetate, 4.8 parts of sodium lignin sulfonate, 6 parts of silane coupling agent KH-570, 12 parts of bentonite, and 15 parts of deionized water;
[0064] A method for preparing real stone paint comprises the following steps:
[0065] The first step is to weigh the raw materials by mass: 105 parts of natural stone powder, 85 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 2, 10 parts of propylene glycol methyl ether acetate, 4.8 parts of sodium lignin sulfonate, 6 parts of silane coupling agent KH-570, 12 parts of bentonite, and 15 parts of deionized water;
[0066] Step 2: Mix silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume in a container, and stir for 3 hours at 50°C to obtain modified stone powder, wherein the mass ratio of silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume is 6:105:70;
[0067] Step 3: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant and deionized water obtained in Example 2 in a container, and stir for 105 min at a rotation speed of 1800 rpm to obtain a prefabricated liquid;
[0068] The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, and stir at a speed of 1400 rpm for 75 minutes to disperse, then add bentonite to the solution, and continue to stir at a speed of 700 rpm for 40 minutes to mix evenly to obtain a real stone paint.
[0069] The natural stone powder in this embodiment is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:1.8.
[0070] Example 6
[0071] A real stone paint comprises the following raw materials in parts by weight: 120 parts of natural stone powder, 100 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 3, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of silane coupling agent KH-570, 8 parts of bentonite, and 28 parts of deionized water;
[0072] A method for preparing real stone paint comprises the following steps:
[0073] The first step is to weigh the raw materials by mass: 120 parts of natural stone powder, 100 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 3, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of silane coupling agent KH-570, 8 parts of bentonite, and 28 parts of deionized water;
[0074] Step 2: Mix silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume in a container, and stir for 4 hours at 60°C to obtain modified stone powder, wherein the mass ratio of silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume is 8:120:80;
[0075] Step 3: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant and deionized water obtained in Example 3 in a container, and stir for 120 min at a speed of 2000 rpm to obtain a prefabricated liquid;
[0076] The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, and stir at a speed of 1600 rpm for 90 minutes to disperse, then add bentonite to the solution, and continue to stir at a speed of 800 rpm for 50 minutes to mix evenly to obtain a real stone paint.
[0077] The natural stone powder in this embodiment is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:2.4.
[0078] Comparative Example 1
[0079] A real stone paint comprises the following raw materials in parts by weight: 120 parts of natural stone powder, 100 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 3, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of bentonite, and 28 parts of deionized water;
[0080] A method for preparing real stone paint comprises the following steps:
[0081] The first step is to weigh the raw materials according to the mass fractions: 120 parts of natural stone powder, 100 parts of the water-resistant and UV-resistant polyacrylate emulsion obtained in Example 3, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of bentonite, and 28 parts of deionized water;
[0082] Step 2: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant and deionized water obtained in Example 3 in a container, and stir for 120 min at a speed of 2000 rpm to obtain a prefabricated liquid;
[0083] The third step is to add the natural stone powder to the prefabricated liquid obtained in the second step, stir at a speed of 1600 rpm for 90 minutes to disperse, then add bentonite to the solution, continue stirring at a speed of 800 rpm for 50 minutes to mix evenly to obtain a real stone paint.
[0084] The natural stone powder in this embodiment is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:2.4.
[0085] Comparative Example 2
[0086] This comparative example is a polyacrylate emulsion sold by Jinan Feiyue Chemical Co., Ltd.
[0087] A real stone paint comprises the following raw materials in parts by weight: 120 parts of natural stone powder, 100 parts of commercially available polyacrylate emulsion, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of silane coupling agent KH-570, 8 parts of bentonite, and 28 parts of deionized water;
[0088] A method for preparing real stone paint comprises the following steps:
[0089] The first step is to weigh the raw materials according to the mass proportions: 120 parts of natural stone powder, 100 parts of commercially available polyacrylate emulsion, 14 parts of propylene glycol methyl ether acetate, 2.4 parts of sodium lignin sulfonate, 8 parts of silane coupling agent KH-570, 8 parts of bentonite, and 28 parts of deionized water;
[0090] Step 2: Mix silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume in a container, and stir for 4 hours at 60°C to obtain modified stone powder, wherein the mass ratio of silane coupling agent KH-570, natural stone powder and 90% ethanol aqueous solution by volume is 8:120:80;
[0091] Step 3: Mix commercially available polyacrylate emulsion, propylene glycol methyl ether acetate, dispersant and deionized water in a container, and stir for 120 min at a rotation speed of 2000 rpm to obtain a prefabricated liquid;
[0092] The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, and stir at a speed of 1600 rpm for 90 minutes to disperse, then add bentonite to the solution, and continue to stir at a speed of 800 rpm for 50 minutes to mix evenly to obtain a real stone paint.
[0093] The natural stone powder in this embodiment is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:2.4.
[0094] Comparative Example 3
[0095] This comparative example is the real stone paint topcoat sold by Anhui Jiuyan Decoration Materials Co., Ltd.
[0096] The performance of the real stone paint obtained in Examples 4-6 and Comparative Examples 1-2 and the commercially available real stone paint in Comparative Example 3 were tested together, referring to the national standard GB / T23987-2009, and the test results were as follows: 2( The color difference value (Δe) under irradiation conditions of 340nm for 168h was tested with reference to "JG / T24-2018 Synthetic Resin Emulsion Sand Wall Architectural Coatings" for the initial drying crack resistance of real stone paint after construction. The test results are shown in Table 2:
[0097] Table 2
[0098]
[0099] It can be seen from Table 2 that the anti-ultraviolet ability and anti-cracking ability of the real stone paint obtained in Examples 4-6 of the present invention are better than those of the commercially available real stone paint. Comparative Examples 1-2 respectively carried out control experiments on the silane coupling agent KH-570 used in the present invention and the homemade water-resistant and anti-ultraviolet type polyacrylate emulsion. Failure to use the silane coupling agent KH-570 to modify the natural sand and gravel will lead to uneven components of the real stone paint, defects after construction, and easy cracking. Failure to use the water-resistant and anti-ultraviolet type polyacrylate emulsion of the present invention will lead to poor anti-ultraviolet performance of the real stone paint, and the solution will change color under the influence of ultraviolet light after construction. In summary, the real stone paint of the present invention has uniform components, is not easy to crack, has good anti-ultraviolet ability and hydrophobic properties, and can be widely used in the field of architectural decoration.
[0100] The above is a detailed introduction to a kind of real stone paint and its preparation method provided by the present invention. The principle and implementation method of the present invention are described in this article using specific examples. The description of the above embodiments is only used to help understand the method of the present invention and its core idea, including the best mode, and also enables any technician in the field to practice the present invention, including manufacturing and using any device or system, and implementing any combination method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified. In particular, as long as there is no structural conflict, the various features in the embodiments disclosed in the present invention can be used in combination with each other in any way. The fact that these combinations are not exhaustively described in this specification is only for the consideration of omitting space and saving resources. Therefore, the present invention is not limited to the specific embodiments disclosed in the text, but includes all technical solutions falling within the scope of the claims.
Claims
1. A real stone paint, characterized in that: The invention comprises the following raw materials in parts by weight: 90-120 parts of natural stone powder, 70-100 parts of water-resistant and UV-resistant polyacrylate emulsion, 10-14 parts of propylene glycol methyl ether acetate, 2.4-4.8 parts of dispersant, 6-8 parts of silane coupling agent kh-570, 8-12 parts of bentonite, and 15-28 parts of deionized water; Wherein, the water-resistant and UV-resistant polyacrylate emulsion is prepared by the following steps: Step 1, mixing benzotriazole, allyl alcohol and 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine in a container, stirring evenly, and reacting at a temperature of 40-60° C. for 20-24 hours to obtain intermediate 1; Step 2, intermediate 1, acryloyl chloride, triethylamine and N,N-dimethylformamide are mixed in a container, stirred evenly, and reacted at a temperature of 30-60° C. for 1-2 hours to obtain intermediate 2; Step 3, anhydrous ethanol, diethylene glycol butyl ether, and azobisisobutyronitrile are mixed in a container and stirred evenly, then the system temperature is raised to 78°C, and a mixed solution prepared by 4-6g of intermediate 2, 3-5g of hexafluorobutyl acrylate, 45-50g of methyl methacrylate, 1.5-2.5g of methacrylic acid, 25-30g of butyl acrylate and 1.2-2.4g of azobisisobutyronitrile is added dropwise to the container, the dropping time is 1.5-2h, and the temperature is controlled at 78-82°C during the dropping. After the dropping is completed, the reaction is continued for 1.5-2h. After the reaction is completed, the system temperature is lowered to 45-55°C, and N,N-dimethylethanolamine is added to the container for neutralization, and deionized water is added for emulsification to obtain the water-resistant and UV-resistant polyacrylate emulsion.
2. A real stone paint according to claim 1, characterized in that: The amount ratio of benzotriazole, allyl alcohol and 1,3,4,6,7,8-hexahydro-1-methyl-2H-pyrimido[1,2-A]pyrimidine used in step 1 is 0.1 mol: 0.1 mol: 0.18 g.
3. The real stone paint according to claim 1, characterized in that: The amount ratio of intermediate 1, acryloyl chloride, triethylamine and N,N-dimethylformamide used in step 2 is 0.08 mol: 0.09-0.11 mol: 0.12 mol: 40-60 mL.
4. The real stone paint according to claim 1, characterized in that: The dosage ratio of anhydrous ethanol, diethylene glycol butyl ether, azobisisobutyronitrile, homemade mixed solution, N,N-dimethylethanolamine, and deionized water used in step 3 is 24-36g: 3-4g: 0.8-1.6g: 79.7-95.9g: 1.2-2g: 36-44g.
5. A method for preparing the real stone paint according to any one of claims 1 to 4, characterized in that: The method comprises the following preparation steps: The first step is to weigh the raw materials according to the mass proportions: 90-120 parts of natural stone powder, 70-100 parts of water-resistant and UV-resistant polyacrylate emulsion, 10-14 parts of propylene glycol methyl ether acetate, 2.4-4.8 parts of dispersant, 6-8 parts of silane coupling agent KH-570, 8-12 parts of bentonite, and 15-28 parts of deionized water; Step 2: Mix silane coupling agent KH-570, natural stone powder and ethanol solution in a container, and heat and stir to obtain modified stone powder; Step 3: Mix the water-resistant and UV-resistant polyacrylate emulsion, propylene glycol methyl ether acetate, a dispersant, and deionized water in a container, and stir to obtain a prefabricated liquid; The fourth step is to add the modified stone powder obtained in the second step to the prefabricated liquid obtained in the third step, stir and disperse, then add bentonite to the solution, continue to stir and mix evenly to obtain a real stone paint.
6. The method for preparing real stone paint according to claim 5, characterized in that: The natural stone powder is prepared by mixing natural colored sand and natural white sand in a mass ratio of 1:1.1-2.4, and the dispersant is sodium lignin sulfonate.
7. The method for preparing real stone paint according to claim 5, characterized in that: The ethanol solution used in the second step is an ethanol aqueous solution with a volume fraction of 90%. The mass ratio of the silane coupling agent KH-570, natural stone powder and ethanol solution used in the second step is 6-8:90-120:60-80. The heating and stirring conditions are stirring at a temperature of 40-60°C for 2-4 hours.
8. The method for preparing real stone paint according to claim 5, characterized in that: In the third step, the stirring and mixing speed condition is 1600-2000 rpm, and the stirring and mixing time condition is 90-120 min.
9. The method for preparing real stone paint according to claim 5, characterized in that: In the fourth step, the speed of the first stirring and dispersing is 1200-1600 rpm, and the time condition is 60-90 min. The speed of the second stirring and dispersing is 600-800 rpm, and the time condition is 30-50 min.
Citation Information
Patent Citations
Functional really stone paint and preparation method thereof
CN105400342A
Waterborne polyurethane enamel paint and preparation method and application method thereof
CN105504941A